Getting inside consumers' heads - McPhee, Neil (Henry Stewart Talks, 2008)
Why should we want to get inside the heads of consumers?, Qualitative research in context, Neuro linguistic programming (NLP), Observation/Ethnography/Immersion, Neuroscience